Reshaping retirement security lessons from the Global Financial Crisis - Maurer, Raimond; Mitchell, Olivia S.; Warshawsky, Mark. (Oxford : Oxford University Press, 2013)
This title explores the lessons to be learnt for retirement planning and long-term financial security in view of the financial crisis. It rethinks the resilience of defined contribution plans and how defined benefit plans reacted to the crisis.
"A Parachute Research Council book."
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Retirement -- Planning; Finance, Personal; Global Financial Crisis, 2008-2009 -- Social aspects